2020
DOI: 10.1111/bju.14976
|View full text |Cite
|
Sign up to set email alerts
|

Salvage radical prostatectomy following focal therapy: functional and oncological outcomes

Abstract: Objectives To report the oncological and functional outcomes of salvage radical prostatectomy (sRP) after focal therapy (FT). Patients and Methods A retrospective review of all patients who underwent sRP after FT was performed. Clinical and pathological outcomes focussed on surgical complications, oncological, and functional outcomes. Results In all, 34 patients were identified. The median (interquartile range [IQR]) age was 61 (8.25) years. FT modalities included high‐intensity focussed ultrasound (19 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
2
22
1
Order By: Relevance
“…In their study, 77% of men who had focal ablation required 0 or 1 urinary continence pads at 12 months, similar to that reported in the current study (22/23 [96%]); however, the majority of men in their cohort had undergone whole gland ablation therapy which is likely to have a greater impact on continence recovery. Herrera-Caceres et al also recently reported on their cohort of men undergoing surgery after focal ablation [17]. In their study of 34 men, a similar proportion of men were continent after surgery as that reported in RAFT (31/34 [91%]).…”
Section: Comparison With Other Studiessupporting
confidence: 58%
“…In their study, 77% of men who had focal ablation required 0 or 1 urinary continence pads at 12 months, similar to that reported in the current study (22/23 [96%]); however, the majority of men in their cohort had undergone whole gland ablation therapy which is likely to have a greater impact on continence recovery. Herrera-Caceres et al also recently reported on their cohort of men undergoing surgery after focal ablation [17]. In their study of 34 men, a similar proportion of men were continent after surgery as that reported in RAFT (31/34 [91%]).…”
Section: Comparison With Other Studiessupporting
confidence: 58%
“…However, more recent work in 2010 showed continence rates of 71% for sRARP [21]. Salvage RARP after focal therapy had better continence outcomes than whole gland therapy with medium-term continence rates varying from 73% to 91% [14,22]. In our study, full continence rates were greater at all time intervals after focal therapy than after whole gland therapy.…”
Section: Functional Outcomescontrasting
confidence: 41%
“…Salvage RARP after focal therapy had better continence outcomes than whole gland therapy with medium-term continence rates varying from 73% to 91% [14] , [22] . In our study, full continence rates were greater at all time intervals after focal therapy than after whole gland therapy.…”
Section: Discussionmentioning
confidence: 96%